Relationships between socio-demographic variables and psychological empowerment among members of Fadama User Groups (FUGs) in Kankara Local Community, Katsina State, Nigeria - Rilwanu, Aminu; Redzuan, Ma`rof; Abu Samah, Asnarulkhadi (International Organization of Scientific Research, 2014)
This empirical research was designed to focus on the relationship between Socio-demographic variables and psychological empowerment among Fadama User Groups (FUGs) in Kankara Local Community, Katsina State Nigeria. The total of 285 respondents was selected through random sampling techniques. And the instrument use for data collection was structured questionnaire. The collected data was analyzed by using descriptive statistics and chi-square in cross-tabulation form to describe the respondent background through descriptive analysis. Meanwhile cross tabulation was to find out the relationship between Socio-demographic variables and psychological empowerment among Fadama members.